Aerogel made of ternary metal sulfide FeCo2S4 and rGO enhanced with biowaste activated carbon and PANI for supercapacitor - Delawary, Ahmad Reshad; Bubulinca, Constantin; Pechancová, Viera; Kazantseva, Natalia E.; Saha, Petr; Kiefer, Rudolf; Le, Quoc Bao (Frontiers in Energy Research, 2025)
Supercapacitors utilizing activated carbon derived from Brewer’s spent grain (BSG) offer a sustainable and innovative solution for rapid energy storage and release. Pyrolysis using various activation techniques transforms biowastes into highly porous materials with large surface areas, making them ideal for supercapacitor applications. In this study, FeCo2S4 was synthesized and combined with reduced graphene oxide (rGO) to create an aerogel. Brewery biowaste activated carbon (AC) and polyaniline (PANI) were added to enhance the electrochemical properties of the composite electrode material. Those composites morphologies were observed via SEM. Their electrochemical properties were tested using CV, GCD and EIS. The electrochemical performance of the resulting rGO/AC/FeCo2S4@PANI composite was evaluated, achieving a high specific capacitance of 290.57 F/g at 0.5 A/g, comparable to that of the composite without AC. The small charge transfer resistance values of rGO/AC/FeCo2S4 required via full cell testing in this research showed the value of 1.498 Ω, suggesting superior retention. Therefore, AC significantly enhanced cycling stability, with the composite retaining 97.6% of its capacitance after 5,000 cycles.